Dynamic Capability dalam Memperkuat Cooperative Identity dan Keberlanjutan Koperasi: Sebuah Integrative Literature Review - Iwan Mulyana; Tryiis ARR; Ucu Nurwati (J-Coop : Journal of Co-operative, 2026)
Rapid changes in the business environment driven by digitalization, globalization, technological advancement, and increasing market complexity require cooperatives to enhance their adaptive capacity while preserving their identity as member-based organizations. In this context, dynamic capability has emerged as a strategic concept that enables organizations to sense environmental changes, seize opportunities, and transform organizational resources continuously. Nevertheless, studies examining the relationship between dynamic capability, cooperative identity, and cooperative sustainability remain fragmented. This study aims to synthesize the existing literature to explain the role of dynamic capability in strengthening cooperative identity and promoting cooperative sustainability. This study employs an Integrative Literature Review by examining scholarly articles, academic books, and institutional reports collected from reputable academic databases. Data were analyzed using content analysis and thematic analysis to identify key themes, conceptual relationships, and research gaps. The findings indicate that dynamic capability contributes to cooperative sustainability through three interrelated dimensions: sensing, seizing, and transforming. These capabilities enable cooperatives to improve innovation, organizational adaptability, and governance quality in responding to environmental changes. Furthermore, the review identifies cooperative identity as a conceptual mechanism linking dynamic capability and cooperative sustainability. Organizational transformation generates sustainable outcomes only when it remains grounded in cooperative values, principles, democratic governance, and member participation. This study contributes by proposing an integrated conceptual framework connecting dynamic capability, cooperative identity, and cooperative sustainability. The proposed framework extends the application of dynamic capability theory within the cooperative context and offers practical insights for developing adaptive, innovative, and identity-based cooperative transformation strategies.